Theoretical Study on Time Delay of Slow Light by Remodeling SBS Gain and Absorption Spectrum - Qiliang Li; Yong Zhang; Ziyang Wang; Ran Zeng; Tianshu Wang; Miao Hu (Institute of Advanced Engineering and Science, 2012)
In this paper, we perform a theoretical study of processes that demonstrates additional time delay obtained by remodeling Brillouin gain spectrum, and we also study the main influence factors on pulse time delay and broadening, as well as analyze the ways which increases the delay, and further suppresses pulse broadening. The results show that by remodeling Brillouin gain spectrum, one obtains 25% delay improvement over the single intrinsic Brillouin gain spectrum; by deriving the expression of broadening factor, one finds that the increase of intrinsic SBS resonance linewidth leads to the decrease of the broadening quantity which corresponds to the maximum delay. Moreover, the increase of the peak power of absorption spectrum further leads to an increase of pulse delay. When the normalized frequency shift is below a certain value, probe pulse can be compressed; When the second-order gain is positive, pulse will be compressed; when the second-order gain is negative, pulse will become broad. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1543